Analysis of Epidemiological Situation on Leptospiroses in the Amur-River Region. Operational Experience in the Flood Area in 2013, and Forecasting for 2014 - N. V. Breneva; A. K. Noskov; E. Yu. Kiseleva; M. B. Sharakshanov; S. A. Borisov; O. P. Kurganova; L. I. Ivanov; T. V. Gromova; T. A. Zaitseva; V. A. Yanovich; M. V. Afanas’Ev; V. V. Voitkova; et al. (Проблемы особо опасных инфекций, 2014)
For the first time ever mobile SAET units have performed complex investigation of epidemiological situation on leptospiroses in order to provide sanitary-epidemiological welfare of the population in the Amur-River region devastated by high water in 2013. Analyzed have been contemporary published and archival data on morbidity rate and epizootic activity of the natural leptospirosis foci in the Amur-River territory up to 2013. Summarized is the information concerning monitoring over natural focal infections (in particular leptospiroses) in the flooding area, obtained by specialized antiepidemic teams from Irkutsk Research Anti-Plague Institute of Siberia and Far East deployed in Belogorsk town of the Amur Region and Khabarovsk city in 2013. Epizootiological situation during the high water period in the Jewish Autonomous Region has been defined as an extremely adverse, unlike the Khabarovsk Territory and the Amur Region where epizootic process is less expressed. Therewith aggravation of epidemiological situation on leptospiroses in the Amur-River Region in 2014 is not ruled out.